The Ignored Impact of the Livestock Sector on Climate Change: An Analysis from the Perspective of International Law - Melina Moreira Campos Lima (German Law Journal)
Climate change stands as the paramount challenge confronting humanity in the contemporary era. Attempting to address the problem, the main sectors responsible for it have been subject to domestic or international policies and laws aimed at reducing greenhouse gas (GHG) emissions, except one: livestock. Given that animal-sourced food production contributes a large portion of GHG emissions, this Article aims to analyze the impacts that the exclusion of the livestock sector, in efforts to tackle climate change, would have on compliance with international treaties on the subject, especially the Paris Agreement. One conclusion reveals that state parties, by ignoring the sector, will violate several articles of the Agreement, which will likely lead to the failure of its main purpose of holding the increase in the global average temperature to well below 2°C.